Hospital-based surveillance of severe rotavirus gastroenteritis and rotavirus strains in young Taiwanese children - Yen-Hsin Kung (Journal of the Formosan Medical Association, 2020)
Background/Purpose: Rotavirus remains a leading cause of pediatric gastroenteritis-related hospitalization. Surveillance studies have revealed that several major rotaviral genotypes are responsible for most cases of rotavirus gastroenteritis (RVGE). This study aimed to understand the characteristics of acute gastroenteritis (AGE) caused by rotavirus in young children in Taiwan. Methods: Ten hospitals in Taiwan were subjected to prospective hospital-based AGE surveillance during 2014–2017, and children younger than 5 years old who were hospitalized due to AGE were enrolled in the study. Medical and demographic variables were recorded and analyzed, and stool specimens were collected for rotavirus identification and genotyping via real-time RT-PCR. Non-rotavirus AGE age-matched controls were enrolled. Results: Surveillance identified 4747 young children hospitalized with AGE during this study period. The median age of these patients was 2.0 years. Rotavirus was detected in stool samples from 518 patients (10.9%). The prevalent months of RVGE in 2014, 2015, and 2017, wherein the rotavirus positivity rates exceeded 30%. The most common serotypes were G3P[8] (303/518, 58.9%) and G1P[8] (86/518, 16.6%). The percentage of G3P[8] increased from 4.9% in 2014 to 74.3% in 2016 (P < 0.0001), whereas the percentage of G1P[8] decreased from 61.0% in 2014 to 22.5% in 2015 (P < 0.0001). Compared with G3P[8], G1P[8] was associated with a significantly higher C-reactive protein level (P < 0.05). Conclusion: Rotavirus remains a notable pathogenic etiology of childhood AGE and the G3P[8] serotype was dominant in Taiwan. This study highlighted the importance of rotavirus surveillance to ensure protective effectiveness against the circulating strains.